Iranian Nursing Students' Perceptions of Nursing and The Ideal Career: A Descriptive Comparative Study - Khademian; Moattari; Khademian (Kashan University of Medical Sciences, 2016)
Background Identification of the attributes of nursing and the ideal career, and their similarities and differences, as perceived by nursing students will help to plan strategies to train and retain future nursing workforce. Objectives This study aimed to compare the attributes of nursing with the ideal career, as perceived by nursing students. Materials and Methods This cross-sectional study was conducted from April to June 2012 at Shiraz University of Medical Sciences. The participants were 181 undergraduate nursing students (127 females and 54 males) selected using a census method. Data were collected using a questionnaire and analyzed using descriptive statistics, analysis of variance, Spearman correlation, and Wilcoxon rank sign test. Results Perceptions of nursing and the ideal career were different in nineteen attributes (P < 0.001). Nursing students expected a career which provides them more respect, appreciation, safety, income, power, and facility. Both nursing and an ideal career share an altruistic nature, academic advancement, a desire to please God, and somehow low level of excitement. Conclusions Perceptions of nursing were significantly different from those of the ideal career in most of the attributes. Therefore, it is recommended that nurses' income, workplace safety, and sense of being appreciated and respected by all authorities should be improved.